Reconstitution of DNA Segregation Driven by Assembly of a Prokaryotic Actin Homolog - Garner, Ethan C. (2007)
Multiple unrelated polymer systems have evolved to partition DNA molecules between daughter cells at division. To better understand polymer-driven DNA segregation, we reconstituted the three-component segregation system of the R1 plasmid from purified components. We found that the ParR/parC complex can construct a simple bipolar spindle by binding the ends of ParM filaments, inhibiting dynamic instability, and acting as a ratchet permitting incorporation of new monomers and riding on the elongating filament ends. Under steady-state conditions, the dynamic instability of unattached ParM filaments provides the energy required to drive DNA segregation.